Bangus (Chanos Chanos) Fry Counter - Dr. John C. Amar; Glenn J. Frencillo, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2023)
Agriculture has a key role in the Philippines economy, particularly the fisheries industry, which contributes 15% of the country’s overall income. The sector offers significant employment and income for various parts of population, contributes to export earnings, and meets a large portion of the population’s nutritional protein requirements. In terms of employment, the fisheries sector employs over one million people, or about 5% of the nation. The general objective of the study is to develop a portable bangus fry counter for the University of Antique – Hamtic Campus, Hamtic, Antique, and an affordable fry counter for the local fish fry vendor, fish pond owner and others that can benefit in this thesis. The researchers used the Arduino for the operating system and the light censor for the input and the LCD for the output. For the data gathering, the researchers used the ISO 25010 characteristic, the weighted mean formula to solve the mean and the Likert scale. The prototype showed excellent performance in terms of counting the bangus fry quantities. Based on the results of the evaluation, the participants strongly agreed with the functionality, reliability, portability, maintainability, security, compatibility, performance efficiency and usability of the device.